Monetary Policy and External Factors: Empirical Evidence for Association of Southeast Asian Nations 3 - Gan, Pei-Tha; Lee, Nyuk-Ling; Hussin, Mohd Yahya Mohd; Rambeli, Norimah (International Journal of Economics and Financial Issues, 2016)
The motivation for this paper is the external factors can be the important objectives of the monetary policy in a small open economy. This study will extend the standard Taylor rule that initially encompassed output and inflation by adding the exchange rate and terms of trade. By using the augmented Taylor rule, this paper examines exchange rates and terms of trade and determines its empirical validity based on a sample of ASEAN-3 countries. Using the technique of unrestricted error correction model, the findings provide some policy implications; the uncertain movements of the exchange rate and terms of trade can be fine-tuned by the central bank’s interest rate instrument, and the inflation and output are useful policy indicators for monetary decision making of central bank, which eventually promotes the best economic outcomes. Keywords Exchange rate, Monetary policy, Taylor rule, Terms of trade JEL Classifications: C61, E58, E61, F41